Factors affecting village fund management accountability in Indonesia: The moderating role of prosocial behaviour - Rani Eka Diansari; Adiza Alhassan Musah; Jaizah Binti Othman (Cogent Business & Management, 2023)
Previous research separately investigated the relationship between competence of the village official, organizational commitment, leadership, internal control, external pressure, and accountability with village official research objects and only looked at how village officials carried out their functions as members of the organization, namely the village, so they had not fully described how attitudes and tendencies individual social behavior of village officials on the imp Thus, this study tries to fill a gap in research by looking at the link between village officials' accountability and competence, organizational commitment, leadership, internal control, external pressure, and prosocial behavior in a comprehensive research model with prosocial behavior as a moderator. This study was undertaken in all Indonesian communities to assess local finance management accountability. Random sampling was used to acquire survey data. 689 Indonesian village officials were studied. PLS-SEM analyzed data. This study found that village officials' competency, leadership, internal control, and external pressure affect village fund management accountability. Organizational commitment and internal control do not promote local fund management accountability in Indonesia. Village finance management accountability and prosocial conduct regulate and improve leadership. Official leadership, internal control, and prosocial behavior promote village money management accountability. This work advances agency theory, stewardship theory, role theory, quality theory and financial accounting and public sector accounting, particularly in village governance.
Keywords: G3; G4; G0; 650; leadership; organizational commitment; Accountability; competency of village officials; external pressure; internal control; prosocial behaviour